Changing paradigm in Indian ·Banking - Subbarao, P.Srinivas (Gyan Management Journal, 2007)
The Indian banking system has undergone transformation itself from domestic banking to international banking. However, the system requires a combination of new technologies, well treasury management, product diversification, internal control, external regulations and professional as well as skilled human resources to achieve the heights of the international excellence to play its role critically in meetng the globalmchallenges in WTO declarations. This paper mainly concentrates on the Major trends that change the banking industry world over, viz. Consolidation of players through mergers and acquisitions,of new technology, Universal banking human resources in banking, profitability, rural banking and risk management. Banks will have to gear up to meet Stringent pmdential capital adequacy norms under Basel I&II in addition, the Free Trade Agreements (FIA)